Tracer coupling of intrinsically photosensitive retinal ganglion cells to amacrine cells in the mouse retina - Müller, Luis Pérez de Sevilla (2010)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) are a subtype of ganglion cell in the mammalian retina that expresses the photopigment, melanopsin, and drives non-image-forming visual functions. Three morphological subtypes of ipRGCs (M1, M2 and M3) have been described based on their dendritic stratifications in the inner plexiform layer (IPL), but the question of their potential interactions via electrical coupling remains unsettled. In this study, we have addressed this question in the mouse retina, by injecting the tracer Neurobiotin into ipRGCs that were genetically labelled with the fluorescent protein, tdTomato. We confirmed the presence of the M1-M3 subtypes of ipRGCs based on their distinct dendritic stratifications. All three subtypes were tracer-coupled to putative amacrine cells situated within the ganglion cell layer (GCL) but not the inner nuclear layer (INL). The cells tracer-coupled to the M1 and M2 cells were shown to be wide-field GABA-immunoreactive amacrine cells. We found no evidence of homologous tracer-coupling of ipRGCs or heterologous coupling to other types of ganglion cells.